"Complexo banda" : a prática das corporações musicais em Pedro Leolpodo/MG - Ana Carolina Malaquias (2021)
Seeking to analyze music bands as promoters of cultural activity and a source of social and behavioral research, this thesis aims to identify and study elements of the practice of three wind bands in the city of Pedro Leopoldo/MG: Corporação Musical Cachoeira Grande (1912), Corporação Musical São Sebastião de Vera Cruz de Minas (1911) and União Musical Nossa Senhora da Conceição (1932), in order to map sources that allow a narrative of local history, having as axis the power relations, conceptual dynamics and characteristics of the musical practice of the whole "band complex". Through the context of the bands' creation, the power relations existing in the negotiations, the sociability networks present in works composed for these groups, and also in other aspects of the practice, it was possible to perceive which historical, social, economic and cultural elements impacted the way of making music and the wind bands' path until the present day, besides the respective identity characteristics of each group. Seeking to understand the hierarchical relations between the maintaining institutions, conductors and musicians, through the Foucaultian perspective, the imbrications of the micro-physical of power were analyzed, within the negotiations and episodes of daily life and its historiographical trajectory. In this panorama, the conductor and composer Mário Pereira da Luz (1887-1962) is situated as an interband practice, allowing us to map the dynamics of social interactions through the networks of sociability reflected in his compositions. As a methodological process, the study of the practice emerged mainly through the crossing of different sources raised along the process, such as documentary, hemerographic, iconographic and videographic analysis. The research on the theme strengthens the importance of such corporations within the academy, in local contexts, assists in the maintenance, representativeness and valorization of the groups, and in the specific case of the bands that are the object of study, are a relevant record of part of their history and consequently of the city of Pedro Leopoldo. Although the sociocultural, historical and geographical characteristics are strong enough to have a direct impact on the musical activity of the three wind bands throughout their history, the result demonstrated completely different paths and performances in the contemporary world.